Low-temperature nanocubic MgO synthesis from MgCl2·6H2O waste - Patrícia Bodanese Prates; Francielly Roussenq Cesconeto; Francisco Alves Vicente; Tatiana Bendo; Luciana Maccarini Schabbach; Humberto Gracher Riella; Márcio Celso Fredel (Next Nanotechnology)
The Mg(OH)2 and MgO nanomaterials were synthesized by precipitation followed by calcination from the industrial waste MgCl2·6H2O originated from the magnesiothermic reaction of solar-grade silicon (P-waste). A similar synthesis process was carried out in parallel with the commercial precursor MgCl2·6H2O (P-com) to compare the products obtained with precursors. For the synthesis of Mg(OH)2 (1st step), aqueous solutions were prepared (low pH for P-waste and natural pH for P-com). NaOH was used as a precipitating agent, and different synthesis temperatures were evaluated (25, 50, 75, and 90 °C). MgO (2nd step) was obtained through calcination at 500 °C for 30 min of previously synthesized Mg(OH)2. The P-waste and the two synthesis products (Mg(OH)2 and MgO) were chemically, thermally, structurally, and morphologically characterized. The results showed that the P-waste is more soluble in an acidic environment, and both precursors present similar thermal behavior and structural profiles. The Mg(OH)2 obtained in the 1st step of synthesis by both precursors presented the crystalline phases Brucite with lamellar morphology and Halite (NaCl) remained of the precursors. The powders obtained from both precursors in the 2nd step presented the same crystalline phase Periclase (MgO), but different morphologies such as fragmented lamellar for the P-com and cubic for the P-waste. However, the particle size distribution narrows, and the D50 of MgO decreases as a function of increasing the synthesis temperature employed in the 1st step for the P-com. In contrast, the D50 of MgO decreases in the P-waste as a function of low pH. Furthermore, surprisingly, it was observed that the morphology of MgO nanocubes can be obtained from residues and commercial precursors at low calcination temperature and short time (500 °C/30 min) when the Halite remaining from the purification washes is above 4.0% by weight.